Impact of interspecific competition and drought on the allocation of new assimilates in trees. (24th April 2016) - Hommel, R.; Siegwolf, R.; Zavadlav, S.; Arend, M.; Schaub, M.; Galiano, L.; Haeni, M.; Kayler, Z. E.; Gessler, A.
Abstract: In trees, the interplay between reduced carbon assimilation and the inability to transport carbohydrates to the sites of demand under drought might be one of the mechanisms leading to carbon starvation. However, we largely lack knowledge on how drought effects on new assimilate allocation differ between species with different drought sensitivities and how these effects are modified by interspecific competition. We assessed the fate of 13 C labelled assimilates in above‐ and belowground plant organs and in root/rhizosphere respired CO2 in saplings of drought‐tolerant Norway maple ( Acer platanoides ) and drought‐sensitive European beech ( Fagus sylvatica ) exposed to moderate drought, either in mono‐ or mixed culture. While drought reduced stomatal conductance and photosynthesis rates in both species, both maintained assimilate transport belowground. Beech even allocated more new assimilate to the roots under moderate drought compared to non‐limited water supply conditions, and this pattern was even more pronounced under interspecific competition. Even though maple was a superior competitor compared to beech under non‐limited soil water conditions, as indicated by the changes in above‐ and belowground biomass of both species in the interspecific competition treatments, we can state that beech was still able to efficiently allocate new assimilate belowground under combined drought and interspecific competition. This might be seen as a strategy to maintain root osmotic potential and to prioritise root functioning. Our results thus show that beech tolerates moderate drought stress plus competition without losing its ability to supply belowground tissues. It remains to be explored in future work if this strategy is also valid during long‐term drought exposure.